Role of surface-exposed charged basic amino acids (Lys, Arg) and guanidination in insulin on the interaction and stability of insulin–insulin receptor complex. (June 2021) - Lee, Vannajan Sanghiran; Sukumaran, Sri Devi; Tan, Pak Kheong; Kuppusamy, Umah Rani; Arumugam, Bavani
Graphical abstract: Highlights: R22, K29 influence stability of insulin–insulin receptor (I-IR) complex. MD simulation of I-IR and per-residue decomposition validated R22, K29 interaction. Guanidination of insulin (Lys-NHC = NHNH2 ) exerted stronger binding of I to IR. Abstract: Naturally occurring proteins are emerging as novel therapeutics in the protein-based biopharmaceutical industry for the treatment of diabetes and obesity. However, proteins are not suitable for oral delivery due to short half-life, reduced physical and chemical stability and low permeability across the membrane. Chemical modification has been identified as a formulation strategy to enhance the stability and bioavailability of protein drugs. The present study aims to study the effect of charge-specific modification of basic amino acids (Lys, Arg) and guanidination on the interaction of insulin with its receptor using molecular modelling. Our investigation revealed that the guanidination of insulin (Lys-NHC = NHNH2 ) enhanced and exerted stronger binding of the protein to its receptor through electrostatic interaction than native insulin (Lys-NH3 + ). Point mutations of Lys and Arg (R22, K29; R22K, K29; R22, K29R; R22K, K29R) were attempted and the effects on the interaction and stability between insulin/modified insulins and insulin receptor were also analyzed in this study. The findings from the study are expected to provide a better understanding of the possible mechanism of action of the modified protein at a molecular level before advancing to real experiments.